Final Review of the Study on Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #4 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The U.S. Department of Energy's Office of Environmental Management is responsible for managing and cleaning up the waste and contamination at the Hanford Nuclear Reservation, the nation's biggest and most complex nuclear cleanup challenge. At the site, 177 underground tanks collectively contain about 211 million liters of waste that includes high-activity and low-activity materials. At the request of Congress, Final Review of the Study on Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #4 focuses on approaches for treatment and disposal of the supplemental portion of the low-activity waste from the tanks. This review report discusses developments since the publication of Review #3 and provides a summary of public comments on the third committee review report. The authoring committee then shares their views on these comments and whether they change any of the findings or recommendations in the third review report.

Toward a Future of Environmental Health Sciences: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
What could the future of environmental health sciences hold, and what steps might be taken now to guide the field's trajectory? To envision a future research enterprise that integrates environmental health sciences, biomedical science, prevention research, and disease-specific research across the continuum from fundamental discovery research through the application of this research to population health, the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled Towards a Future of Environmental Health Sciences on April 26-27, 2022. This publication summarizes the presentations and discussion of the workshop.

Stronger Food and Drug Regulatory Systems Abroad - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Ensuring the safety of food and the quality and safety of medicines in a country is an important role of government, made more complicated by global manufacturing and international trade. By recent estimates, unsafe food kills over 400,000 people a year, a third of them children under 5, mostly in low- and middle-income countries; every year poor quality medicines cause about 70,000 excess deaths from childhood pneumonia and roughly 8,500 to 20,000 malaria deaths in sub-Saharan Africa alone. The Federal Drug Administration (FDA) Office of Global Policy and Strategy is charged with improving capacity of the agency's foreign counterpart offices and increasing understanding of the importance of regulatory systems for public health, development, and trade. At the request of the FDA, this study sets out a strategy to support good quality, wholesome food and safe, effective medical products around the world. Its goal is to build on the momentum for strengthening regulatory systems and to set a course for sustainability and continued progress. The 2012 report Ensuring Safe Food and Medical Products Through Stronger Regulatory Systems Abroad outlined strategies to secure international supply chains, emphasized capacity building and support for surveillance in low- and middle-income countries, and explored ways to facilitate work sharing among food and medical product regulatory agencies. This new study assess progress made and the current regulatory landscape.

Innovations in the Food System: Exploring the Future of Food: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
On August 720138, 2019, the National Academies of Sciences, Engineering, and Medicine hosted a public workshop in Washington, DC, to review the status of current and emerging knowledge about innovations for modern food systems and strategies for meeting future needs. The workshop addressed different perspectives on the topic of food systems and would build on a workshop on the topic of sustainable diets hosted by the Food Forum in August 2018. This publication summarizes the presentations and discussions from the workshop.

Global Health Transitions and Sustainable Solutions: The Role of Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On June 13201314, 2018, the National Academies of Sciences, Engineering, and Medicine convened a multistakeholder workshop to examine the transitions affecting global health and innovative global health solutions. The goal of bringing these two topics together was to collectively explore models for innovative partnerships and private-sector engagement with the potential to support countries in transition. This publication summarizes the presentations and discussions from the workshop.

Why Indoor Chemistry Matters - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
People spend the vast majority of their time inside their homes and other indoor environments where they are exposed to a wide range of chemicals from building materials, furnishings, occupants, cooking, consumer products, and other sources. Despite research to date, very little is known about how exposures to indoor chemicals across complex chemical phases and pathways affect human health. The COVID-19 pandemic has only increased public awareness of indoor environments and shed light on the many outstanding questions about how best to manage chemicals indoors. This report identifies gaps in current research and understanding of indoor chemistry and new approaches that can be applied to measure, manage, and limit chemical exposures. Why Indoor Chemistry Matters calls for further research about the chemical transformations that can occur indoors, pathways and timing of indoor chemical exposure, and the cumulative and long-term impacts of exposure on human health. Research priorities should consider factors that contribute to measurable environmental health disparities that affect vulnerable populations, such as the age, location, and condition of buildings that can alter exposures to indoor chemicals.

Environmental Chemicals, the Human Microbiome, and Health Risk: A Research Strategy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
A great number of diverse microorganisms inhabit the human body and are collectively referred to as the human microbiome. Until recently, the role of the human microbiome in maintaining human health was not fully appreciated. Today, however, research is beginning to elucidate associations between perturbations in the human microbiome and human disease and the factors that might be responsible for the perturbations. Studies have indicated that the human microbiome could be affected by environmental chemicals or could modulate exposure to environmental chemicals. Environmental Chemicals, the Human Microbiome, and Health Risk presents a research strategy to improve our understanding of the interactions between environmental chemicals and the human microbiome and the implications of those interactions for human health risk. This report identifies barriers to such research and opportunities for collaboration, highlights key aspects of the human microbiome and its relation to health, describes potential interactions between environmental chemicals and the human microbiome, reviews the risk-assessment framework and reasons for incorporating chemical2013microbiome interactions.

The Role of Nonpharmacological Approaches to Pain Management: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Pain is a leading cause of disability globally. The dramatic increase in opioid prescriptions within the past decade in the United States has contributed to the opioid epidemic the country currently faces, magnifying the need for longer term solutions to treat pain. The substantial burden of pain and the ongoing opioid crisis have attracted increased attention in medical and public policy communities, resulting in a revolution in thinking about how pain is managed. This new thinking acknowledges the complexity and biopsychosocial nature of the pain experience and the need for multifaceted pain management approaches with both pharmacological and nonpharmacological therapies. The magnitude and urgency of the twin problems of chronic pain and opioid addiction, combined with the changing landscape of pain management, prompted the National Academies of Sciences, Engineering, and Medicine to convene a workshop on December 420135, 2018, in Washington, DC. The workshop brought together a diverse group of stakeholders to discuss the current status of nonpharmacological approaches to pain management, gaps, and future directions. This publication summarizes the presentations and discussions from the workshop.

Reducing Impacts of Food Loss and Waste: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Even as malnutrition in the form of hunger and obesity affect the health and well-being of millions of people worldwide, a significant amount of food is lost or wasted every day, in every country, and at every stage in the supply chain from the farm to the household. According to a 2011 estimate by the Food and Agriculture Organization of the United Nations (FAO), about one-third of food produced is lost or wasted globally. Beyond quantity estimates, however, less is known about the impacts on farmers, food prices, food availability, and environment of reducing food loss and waste. On October 17, 2018, the National Academies of Sciences, Engineering, and Medicine organized a workshop to examine key challenges that arise in reducing food loss and waste throughout the supply chain and discussed potential ways to address these challenges. This publication summarizes the presentations and discussions from the workshop.

Health-Focused Public–Private Partnerships in the Urban Context: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
To draw attention to health determinants and health inequities among populations that live in urban environments and to explore challenges faced in establishing urban population health, the Forum on Public-Private Partnerships for Global Health and Safety hosted a 1.5-day workshop on the role of health-focused public-private partnerships (PPPs) in the urban context. The workshop, held June 13-14, 2019, in Washington, DC, aimed to illuminate some of the intervention strategies that have been designed to attenuate these urban health issues and highlighted the importance of PPPs and urban-level governance in remediation efforts. By facilitating discussion among participants in both the public and private sectors, as well as among policy makers, the workshop served as a platform to share best practices on how to address health challenges through interventions that target healthier urban populations. This publication highlights the presentations and discussion of the workshop.

Evidence-Based Practice for Public Health Emergency Preparedness and Response - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
When communities face complex public health emergencies, state local, tribal, and territorial public health agencies must make difficult decisions regarding how to effectively respond. The public health emergency preparedness and response (PHEPR) system, with its multifaceted mission to prevent, protect against, quickly respond to, and recover from public health emergencies, is inherently complex and encompasses policies, organizations, and programs. Since the events of September 11, 2001, the United States has invested billions of dollars and immeasurable amounts of human capital to develop and enhance public health emergency preparedness and infrastructure to respond to a wide range of public health threats, including infectious diseases, natural disasters, and chemical, biological, radiological, and nuclear events. Despite the investments in research and the growing body of empirical literature on a range of preparedness and response capabilities and functions, there has been no national-level, comprehensive review and grading of evidence for public health emergency preparedness and response practices comparable to those utilized in medicine and other public health fields. Evidence-Based Practice for Public Health Emergency Preparedness and Response reviews the state of the evidence on PHEPR practices and the improvements necessary to move the field forward and to strengthen the PHEPR system. This publication evaluates PHEPR evidence to understand the balance of benefits and harms of PHEPR practices, with a focus on four main areas of PHEPR: engagement with and training of community-based partners to improve the outcomes of at-risk populations after public health emergencies; activation of a public health emergency operations center; communication of public health alerts and guidance to technical audiences during a public health emergency; and implementation of quarantine to reduce the spread of contagious illness.

Faith–Health Collaboration to Improve Community and Population Health: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
On March 22, 2018, the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine the collaboration between the faith and health sectors, and to highlight the unique opportunities these collaborations offer to help improve population health outcomes. This publication summarizes the presentations and discussions from the workshop.

Respiratory Health Effects of Airborne Hazards Exposures in the Southwest Asia Theater of Military Operations - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
More than 3.7 million U.S. service members have participated in operations taking place in the Southwest Asia Theater of Military Operations since 1990. These operations include the 1990-1991 Persian Gulf War, a post-war stabilization period spanning 1992 through September 2001, and the campaigns undertaken in the wake of the September 11, 2001, attacks. Deployment to Iraq, Kuwait, Saudi Arabia, Bahrain, Gulf of Aden, Gulf of Oman, Oman, Qatar, the United Arab Emirates, and Afghanistan exposed service members to a number of airborne hazards, including oil-well fire smoke, emissions from open burn pits, dust and sand suspended in the air, and exhaust from diesel vehicles. The effects of these were compounded by stressors like excessive heat and noise that are inevitable attributes of service in a combat environment. Respiratory Health Effects of Airborne Hazards Exposures in the Southwest Asia Theater of Military Operations reviews the scientific evidence regarding respiratory health outcomes in veterans of the Southwest Asia conflicts and identifies research that could feasibly be conducted to address outstanding questions and generate answers, newly emerging technologies that could aid in these efforts, and organizations that the Veterans Administration might partner with to accomplish this work.

Options for Reducing Lead Emissions from Piston-Engine Aircraft - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Small gasoline-powered aircraft are the single largest emitter of lead in the United States, as other major emission sources such as automobile gasoline have been previously addressed. A highly toxic substance that can result in an array of negative health effects in humans, lead is added to aviation gasoline to meet the performance and safety requirements of a sizable portion of the country2019s gasoline-powered aircraft.Significantly reducing lead emissions from gasoline-powered aircraft will require the leadership and strategic guidance of the Federal Aviation Administration (FAA) and a broad-based and sustained commitment by other government agencies and the nation2019s pilots, airport managers, aviation fuel and service suppliers, and aircraft manufacturers, according to a congressionally mandated report from the National Academies of Sciences, Engineering, and Medicine.While efforts are underway to develop an unleaded aviation fuel that can be used by the entire gasoline-powered fleet, the uncertainty of success means that other steps should also be taken to begin reducing lead emissions and exposures, notes the report, titled TRB Special Report 336: Options for Reducing Lead Emissions from Piston-Engine Aircraft.Piston-engine aircraft are critical to performing general aviation (GA) functions like aerial observation, medical airlift, pilot training, and business transport. Other GA functions, such as crop dusting, aerial firefighting, search and rescue, and air taxi service, have particular significance to communities in rural and remote locations.Accompanying the report is a three-page highlight summary that provides a condensed version of the findings.

A Research Roadmap for Transportation and Public Health - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
States and localities are beginning to recognize and act on the connection between health and transportation. A growing number of entities have produced a number of resources, guidance documents, and strategic plans on the topic.The TRB National Cooperative Highway Research Program's NCHRP Research Report 932: A Research Roadmap for Transportation and Public Health builds upon this body of work to provide a plan for funding research over the next decade that can lead to greater consideration of health issues in transportation contexts.The report includes an Implementation Plan that is outlined in the Health and Transportation Research Roadmap presentation as well as a document on the research methods and background materials from the project.The 10-year strategic Roadmap will provide a broad overview of highly relevant research needs as well as implementable tools for state DOTs and partners at the intersection of transportation and public health in the U.S.

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all. Global Health and the Future Role of the United States identifies global health priorities in light of current and emerging world threats. This report assesses the current global health landscape and how challenges, actions, and players have evolved over the last decade across a wide range of issues, and provides recommendations on how to increase responsiveness, coordination, and efficiency 2013 both within the U.S. government and across the global health field.

Social Isolation and Loneliness in Older Adults: Opportunities for the Health Care System - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Social isolation and loneliness are serious yet underappreciated public health risks that affect a significant portion of the older adult population. Approximately one-quarter of community-dwelling Americans aged 65 and older are considered to be socially isolated, and a significant proportion of adults in the United States report feeling lonely. People who are 50 years of age or older are more likely to experience many of the risk factors that can cause or exacerbate social isolation or loneliness, such as living alone, the loss of family or friends, chronic illness, and sensory impairments. Over a life course, social isolation and loneliness may be episodic or chronic, depending upon an individual's circumstances and perceptions. A substantial body of evidence demonstrates that social isolation presents a major risk for premature mortality, comparable to other risk factors such as high blood pressure, smoking, or obesity. As older adults are particularly high-volume and high-frequency users of the health care system, there is an opportunity for health care professionals to identify, prevent, and mitigate the adverse health impacts of social isolation and loneliness in older adults. Social Isolation and Loneliness in Older Adults summarizes the evidence base and explores how social isolation and loneliness affect health and quality of life in adults aged 50 and older, particularly among low income, underserved, and vulnerable populations. This report makes recommendations specifically for clinical settings of health care to identify those who suffer the resultant negative health impacts of social isolation and loneliness and target interventions to improve their social conditions. Social Isolation and Loneliness in Older Adults considers clinical tools and methodologies, better education and training for the health care workforce, and dissemination and implementation that will be important for translating research into practice, especially as the evidence base for effective interventions continues to flourish.

Implications of the California Wildfires for Health, Communities, and Preparedness: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
California and other wildfire-prone western states have experienced a substantial increase in the number and intensity of wildfires in recent years. Wildlands and climate experts expect these trends to continue and quite likely to worsen in coming years. Wildfires and other disasters can be particularly devastating for vulnerable communities. Members of these communities tend to experience worse health outcomes from disasters, have fewer resources for responding and rebuilding, and receive less assistance from state, local, and federal agencies. Because burning wood releases particulate matter and other toxicants, the health effects of wildfires extend well beyond burns. In addition, deposition of toxicants in soil and water can result in chronic as well as acute exposures. On June 4-5, 2019, four different entities within the National Academies of Sciences, Engineering, and Medicine held a workshop titled Implications of the California Wildfires for Health, Communities, and Preparedness at the Betty Irene Moore School of Nursing at the University of California, Davis. The workshop explored the population health, environmental health, emergency preparedness, and health equity consequences of increasingly strong and numerous wildfires, particularly in California. This publication is a summary of the presentations and discussion of the workshop.

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.

Criteria for Selecting the Leading Health Indicators for Healthy People 2030 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Every ten years, the Department of Health and Human Service's Healthy People Initiative develops a new set of science-based, national objectives with the goal of improving the health of all Americans. Defining balanced and comprehensive criteria for healthy people enables the public, programs, and policymakers to gauge our progress and reevaluate efforts towards a healthier society. Criteria for Selecting the Leading Health Indicators for Healthy People 2030 makes recommendations for the development of Leading Health Indicators for the initiative's Healthy People 2030 framework. The authoring committee's assessments inform their recommendations for the Healthy People Federal Interagency Workgroup in their endeavor to develop the latest Leading Health Indicators. The finalized Leading Health Indicators will establish the criteria for healthy Americans and help update policies that will guide decision-marking throughout the next decade. This report also reviews and reflects upon current and past Healthy People materials to identify gaps and new objectives.